Vildsvinsskador inom jordbruket : hur stora är förlusterna? - Persson, Patrik (SLU/Dept. of Economics, 2010)
Problems with wild boars are increasing in Sweden and some people argue that the wild boar population must decrease. This is mostly the opinion by farmers, while the hunters want more wild boars in Sweden. Today the population is the strongest in the south of Sweden and in the eastern parts of the country. However the population is growing stronger in other parts of Sweden as well. The population origins from these areas where they escaped from pens around 1970. There are no calculations on how many wild boars there are in Sweden today, but it is defiantly more than 100 000.